THE EXISTENCE OF TADUT AND ANDAI – ANDAI IN SOUTH BENGKULU SOCIETY - Sady, Rominto; Andayani, Andayani; Widodo, Sahid Teguh (English Department FBS UNP, 2017)
The study aims to describe the existence of tadut and andai-andai in South Bengkulu society. The research problem discussed is how the existence of tadut and andai-andai in South Bengkulu society. This research conducts phenomenology appoarch with qualitatively descriptive method. The results of this research showed that tadut and andai-andai in South Bengkulu began to be abandoned by the people around there. This is indicated with rarely performances of the folklores and the young generation prefers to western culture than them. The capable efforts to preserve the two folklores are the synergy between the community of people and the government in making inheritance a more interesting, for example by making it in the form of audio visuals, establishing customary institutions in each village, documenting the two folklores, holding their competencies, and including them into the school curriculum.